TRENDS IN PRESS COVERAGE OF FEMINIST ACTIVITY IN THE UAE MEDIA: AN ANALYTICAL STUDY - Makki, Alaa; Juinat, Marcel Issa Al (International Journal of Research -GRANTHAALAYAH, 2021)
This study seeks to shed light on Arab societies in general and the Emirati society in particular, as we find that customs and traditions have given the conservative form of women, Which, in turn, is reflected in the entirety of its relations, and its social and cultural processes in particular are closely related to the media institution that reproduced this model by adopting conservative contents, except in very few cases, which is often associated with some feminist institutions. In this study, the researchers focused on identifying the most important shapes, templates, trends, and areas occupied by all of these coverage. And then determine its contents and meanings. that is through analyzing the coverage and its types and all the arts of journalistic editing, News coverage is made up of the type of news and report, while the explanatory coverage is by the type of press article Investigation and press dialogue, as for the documentary coverage, it is related to the means of highlighting, whether they are news or non-news photos, figures and drawings.